Development of food products based on cyclodextrins - Gribkova V. A.; Mitroshina D. P.; Slavyanskiy A. A.; Nikolaeva N. V.; Litvyak V. V.; Shilov V. V. (Vestnik MGTU)
The production of a new generation of food products with pre-established quality requirements is one of the priority areas of development of the modern food industry. It is especially important to note the need for a more complete use of socially significant food products for these purposes, which also includes white sugar. Crystalline white sugar is not only an energy-important component of nutrition, but also a raw material for a number of food industry sectors. These include, for example, confectionery production, where the annual demand for it is about 1 mln tons. Imparting new nutritional properties to sugar will expand the range of products based on it. The use of iodine may be relevant in this area, since the problem of iodine deficiency in Russia still exists and has not lost its relevance. However, the implementation of such an approach is associated with technological features, including the creation of iodized products. Expanding ideas on how to solve this problem has required appropriate analysis and substantiated research for a deeper understanding of it. Moreover, special attention has been paid to the mechanism of iodine encapsulation when creating new sugar-containing products on its basis. Preliminary approaches to this problem have shown the possibility of using starch production products – cyclodextrins (CD) – for this purpose. Therefore, this paper not only examines their main properties and features, but also attempts to understand the mechanism of complex formation of CD with iodine. The results obtained have shown the prospects for using β-CD in the food industry to expand the range of new sugar-containing products and, in particular, their importance in solving the problem of iodine deficiency.